Diagnostic challenges and future perspectives in fracture-related infection. (June 2018) - Morgenstern, Mario; Kühl, Richard; Eckardt, Henrik; Acklin, Yves; Stanic, Barbara; Garcia, Meritxell; Baumhoer, Daniel; Metsemakers, Willem-Jan
Abstract: Fracture-related infection (FRI) is one of the most challenging complications in orthopaedic trauma surgery. It has severe consequences for patients and an important socio-economic impact. FRI has distinct properties and needs to be addressed interdisciplinary. Since criteria for the diagnosis of FRI are not standardized, an expert panel recently proposed a definition for FRI. In this review the current diagnostic modalities and an interdisciplinary diagnostic algorithm based on this recently published definition, are presented and future diagnostic techniques discussed. Since to date, there is no single universal diagnostic test available that gives the clinician the definitive diagnosis of FRI, it is mandatory to follow a standardized diagnostic algorithm to correctly diagnose FRI.